THE EFFECT OF DIFFERENT ZONING IN A CLOSED-HOUSE CAGE ON MICROCLIMATE CONDITIONS AND BROILER PERFORMANCE - Rahmawati, Sitti; Mozin, Selvy; Damayanti, Andi Pertiwi; Hatta, Ummiani; Sarjuni, Sri; Adjis, Moh. Asril (Universitas Tadulako, 2024)
Closed-house cages have zones in them that have different conditions. Zoning in cages has different temperatures, humidity, speed, and ammonia levels and affects broiler performance. This study aims to determine the effect of different zoning on microclimate conditions and broiler performance in closed-house cages. This research was carried out from June 9, 2023 – to July 6, 2023, at the closed-house cage “Chicken Farm Janna” in Taipa Village, North Palu District, Palu City, Central Sulawesi Province. This study used 396 broiler samples aged 1-28 days with a DOC (Day-old chick) weight of ± 37 grams/head. The strain used is Lohman produced by PT. Japfa Comfeed Indonesia. This study used a t-test with 2 treatments and 9 repeats. The treatment studied is Z1 = Zone 1-60 meters from the inlet and Z2 = Zone 60-120 meters from the inlet. The results of the t-test show that different zoning has a significant influence (t count >t table) on microclimate conditions and broiler performance in closed-house cages. Different zoning exerts a real influence on microclimate conditions and the performance of broilers in closed-house cages. In the closed house cage, the zone opposite the inlet (zone 2) results in a temperature rise, a rise in ammonia levels, a drop in humidity, a loss in body weight, and an increase in mortality.